Forests and water: some sugested strategic directions for CIFOR - Frost, P. (Center for International Forestry Research, 2003)
This discussion paper proposes some strategic directions for CIFOR on the theme of Forests and Water, principally in the context of the CGIAR Global Challenge Program on Water and Food. Within this program, CIFOR may have a comparative research advantage on issues of governance systems; the links between forests, water and livelihoods; and environmental service functions of forests in relation to water production. More broadly, CIFOR has proposed raising awareness of contemporary issues on the relationships between forests and water for policy and management; assembling and disseminating the best available knowledge on the influence of forest cover and land-use practices on water yield, water quality, erosion, sedimentation, and flooding; and targeting research on key forest-water relationships. Current policies on land management in relation to water production are based on a number of long standing misperceptions about the links between forests and hydrological functioning. These myths are summarised alongside empirical findings and counter-myths. The elements of a strategy for establishing CIFOR's profile and activities in this area are laid out. The strategy aims to build on CIFOR's strengths in areas such as natural resource economics, analysis of the impacts of forestry and extra-sectoral policies on resource management, institutional arrangements and dynamics related to the use of forest resources, rural sociology and participatory development, and environmental services received from forests. Some specific research questions are identified in relation to these themes. The strategy emphasises the need to develop strategic partnerships in this field, to develop those areas in which CIFOR currently lacks expertise, and to undertake some short-term, high-profile reviews and syntheses that will establish CIFOR’s standing in this field.